1642 Describing the use of Off-Label and not Approved Medications in a Neonatal Intensive Care Unit in South Brazil. (October 2012) - Carvalho, CG; Ribeiro, M; Bonilha, M; Jr, M Fernandes; Procianoy, RS; Silveira, RC
Abstract : Background and Aims: It is known that unlicensed medicines (unapproved) or used other way than directed in the label (off-label use) are widely prescribed in children. In the NICU, the severity of the patient justifies this type of prescription, evoking the risk-benefit ratio. We aimed to analyze the exposure to unapproved or off-label drugs in NICU in a tertiary university hospital in southern Brazil. Method: A descriptive cohort of drugs prescribed during hospitalization for 129 patients within 6 weeks. The drugs were classified as non-approved, and off-label for the dose, frequency, presentation, age or indication, according to FDA-approved e-lary. Results: We identified 318 items of prescriptions for 61 patients - an average of 5 items/patient, 68 patients without medication. Prevalence of 7.5% for unapproved drugs and 27.7% for off-label, and the more prevalent off-label use was regarding to age - 19.5%. It was computed 57 medications - one patient used 10 off-label drugs during hospitalization. The prevalence of off-label uses was higher in infants < 35 weeks (p=0.00). Sepsis, malformation and extreme prematurity were the main causes to prescribe an off-label medication (p=0.00). Conclusion: Neonates exposed to off-label drugs in NICU had more severe disease, and because it is known that newborns, especially premies, use many drugs, it is necessary to prioritize research in the pharmacotherapy of this population so vulnerable.